Bioresorbable Implants in Reduction of Paediatric Zygomaticomaxillary Complex Fractures Concurrent With Internal Orbital Reconstruction. Issue 7 (29th October 2022) - Zhao, Yiping; Sun, Jing; Li, Zhengkang; Deng, Yuan
Abstract : Purpose: To evaluate the clinical effectiveness and safety of bioresorbable implants for treating paediatric zygomaticomaxillary complex (ZMC) fractures with concomitant orbital floor defects. Methods: A retrospective review of paediatric patients who underwent ZMC repair with concomitant orbital floor fractures with bioresorbable implants in Shanghai Ninth People's Hospital from July 2015 to June 2019 was performed. The primary outcome measures included ocular motility, diplopia, enophthalmos, facial deformities, and restricted mouth opening, as well as complication rates. Pre- and post-operative computed tomography scans were obtained for clinical diagnosis and surgical effectiveness. Results: Twenty two children were included in this study. Facial deformities were corrected in all 22 cases by surgical reconstruction postoperatively, and the average relative distance of Portals point-Zygomaxillare and Anteriornasalspine-Zygomaxillare were 1.3 ± 0.6mm ( P = 0.22) and 1.2 ± 0.5mm ( P = 0.19). The eye movement restored to normal in 13 patients. The mean amount of relative enophthalmos was 1.0 ± 0.4 mm ( P = 0.12). 12 cases had complete resolution of diplopia postoperatively at the extremes of the gaze, and 1 case presented persistent diplopia on the down gaze as before, but from level III to level I. Facial numbness was resolved completely in 6 cases, and 2 cases presented with persistent numbness but relieved significantly. The average Hounsfield units of RapidSorb plates and OrbFloor PI were 154 ± 5 and 99 ± 4 respectively on computed tomography image obtained 1 week postoperatively, which showed no obvious difference compared with 0.5 year postoperatively ( P > 0.1). Hounsfield units of implants gradually declined around 1 year postoperatively. Hounsfield units of RapidSorb plates (20 ± 1) were consistent with periorbital tissue during postoperative 2-year follow-up, and Hounsfield units of OrbFloor PI (19 ± 1) were consistent with periorbital tissue during postoperative 1.5-year follow-up. No patients had severe sequelae or implant related complications postoperatively. None of bone nonunion, malunion, infection or rejection occurred during the follow-up periods. Conclusions: Open reduction and internal fixation for the treatment of ZMC fracture have achieved significant improvement in functional and cosmetic outcomes postoperatively. Bioresorbable materials have been proved to be effective and safe in the treatment of children's ZMC and orbital wall fractures.